INISIASI PEMBENTUKAN KELEMBAGAAN UKM PEMBUATAN SAGU, MENAMBAHKAN NILAI EKONOMI DI KELURAHAN GURAPING KECAMATAN OBA UTARA - Johan Fahri; Ikrima. M. Mustafa; Musdar Muhammad (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
The problems faced by making food and drink are sago, Guraping village, namely the scarcity of raw materials (cassava / cassava) other than being planted in other regions, the problem of raw materials in a part of the land to grow cassava which is increasingly narrow and does not have land, besides that the management management system still uses traditionally, sales management there are still individuals in the do, there is no institution that regulates the management of marketing and continuation of sago making in this Guraping area, so an institution is created to manage and manage food making, namely sago in Guraping village. The methods of service are: lectures, paraktek and mentoring and monitoring, The results of the service of this service activity were attended by as many as 29 located at the Guraping village office. To increase production and management, an institution was created/ formed.